Evaluation of light microscopy to localise the site of haematuria. Issue 3 (March 1991) - Rath, B; Turner, C; Hartley, B; Chantler, C
Abstract : Red cell morphology was examined by light microscopy in 122 urine specimens from 99 patients with haematuria in an attempt to define the site of origin. Altogether 84% of glomerular bleeding and 91% of non-glomerular bleeding was correctly assigned according to diagnoses determined by renal biopsy in 51 patients and clinically in 48. The test should be interpreted with caution as both false positive and false negative results were observed, some in the same individual with unchanged pathology at different times. No advantage of phase contrast over bright field microscopy was apparent even when examining uncentrifuged urines.